Flow-induced vibration analysis of a vehicle's front side window glass. (April 2019) - He, Yinzhi; Andonov, Andon A.; Shi, Zihao; Blumrich, Reinhard; Yang, Zhigang; Wiedemann, Jochen
This study analyses the flow-induced vibration of a car's front side window glass. The following working steps were carried out: experimental modal analysis to yield the dynamic characteristics of the system; wind tunnel experiments and corresponding numerical simulations with a computational fluid dynamics (CFD) code to acquire the pressure field including the fluctuations on the side glass; and a MATLAB implementation of the vibration velocity response calculated with the Corcos model and Mellen elliptical model. The MATLAB model calculates the averaged vibration velocity response by means of the pressure loading from the wind tunnel test or from the CFD simulations as well as by means of the result of the experimental modal analysis. The hereby calculated vibration response of the side glass has been validated by the results of laser Doppler vibrometer measurements in the wind tunnel. Through parameter study with the MATLAB algorithm, it was found that flow convective velocity with U c = 0.6*U, flow decay rates with α x = 0.1 and α z = 0.77 could be considered as the suitable values for the structure vibration velocity response calculation in this type of flow with a low Mach number.